FREQUENCY OF UNERUPTED MANDIBULAR THIRD MOLAR IN MANDIBULAR ANGLE FRACTURES - Qurat Ul Ain; Tariq Javed; Arsalan Wahid (Journal of University Medical & Dental College, 2019)
AIMS AND OBJECTIVES: To determine the frequency of patients of mandibular angle fracture having unerupted mandibular third molar. DURATION: September 2016 to February 2017 SETTINGS: Out-patient Madinah Teaching Hospital, Faisalabad. MATERIAL & METHODS: This study enrolled 83 cases of mandibular angle fractures(both genders & 20 to 50 years) diagnosed clinically and radiographically who gave their consent to be a part of this study. Fracture side was diagnosed by history, examination and radiographs (orthopantomogram) and the status of whereas mandibular third molar (i.e., erupted or unerupted) on the side of fracture as well as on the non-fractured side was seen through clinical and radiographical examination. RESULTS: Out of the 83 patients with mandibular angle fracture, 68 patients were having an unerupted mandibular third molar while 15 patients were having an erupted mandibular third molar. Thus, a patient having mandible with unerupted 3rdmolar have shown increased risk (1.41 times) of mandibular angle fractures as compared to the risk of fracture of mandible with erupted mandibular 3rdmolar. CONCLUSION: An unerupted mandibular third molar tooth (M3) increases the risk and chances of mandibular angle fracture.